Spuścizna po Henryku Beresce. Kilka uwag nad polskimi i niemieckimi zasadami opracowywania archiwów osobistych - Błażej Kaźmierczak (Biblioteka)
The author discusses his comparative analysis of Polish and German archival thought related to processing personal archives. The motive behind the present considerations was the literary and archival legacy of Henryk Bereska, one o f the most eminent translators of Polish literature into the German language. A concise introduction presents briefly the life of H. Bereska and describes the nature of the body of archival work currently held at the university library of Viadrina University in Frankfurt/Oder. Further, the author proceeds to analyze the methods employed for processing personal archives in Poland and in Germany. The most favourable processing methodology created by the team headed by H. Bereska was worked out as the result of the combination of the techniques elaborated in the two aforementioned methodological schools. The approach to processing the body of literary work of the translator was done according to Polish rules for physical ordering of literary legacies and German rules for making up inventories of the processed material. The article also presents the integrated, open Kalliope database, a tool used in the inventory making process employed for documents included in the legacy.